Oldhams mark 50th in grand style (Raton Range Raton, New Mexico, 1988)
Newspaper Article on the 50th Anniversary of Nathan and Juanita Oldham.
Master list item #: 10
File location is in the Raton File Cabinet
Keywords: Oldham, Nathan "Red"; Oldham, Juanita; Holiday Inn; History -- Raton, New Mexico; Biography; Local History; Life and Customs; Anniversary; Celebration; Marriage; Raton, New Mexico; Amarillo, Texas; Lubbock, Texas; Burleson, Texas; Morse, Texas; Red River, New Mexico; Eagle Nest, New Mexico; Cimarron, New Mexico; Springer, New Mexico; Maxwell, New Mexico; Puerto Rico